1952: Ten years after. (1st November 2020) - Rabinowitch, Eugene
ABSTRACT: Ten years after the first sustained nuclear chain reaction, the author surveys a bleak landscape in which few beneficial applications of nuclear power have been achieved but many resources have been devoted to new and more powerful nuclear weapons.